How to reflect more effectively in online video learning: Balancing processes and outcomes. (14th August 2021) - Liu, Zheyu; Yin, Hongbiao; Cui, Weijin; Xu, Boyu; Zhang, Mingchang
Abstract: Designing reflective activities for online video learning could enhance learning outcomes and, to some extent, influence learning processes (ie, attentional processes and emotional experiences). It is necessary to select different levels of reflective activities in online video learning according to learning processes and outcomes. This study examined to what extent different levels of reflection may affect the learning outcomes, and further explored the impact of reflection on learning processes. Participants, comprising 60 undergraduates, were randomly and equally assigned to two different groups: a reflection group and a critical reflection group, and each group member completed specific learning tasks. The results of the learning outcomes showed that critical reflection led to better transfer performance than reflection, but retention performance was the same in both conditions. Regarding process measures, eye‐tracking data indicated that the embedding of critical reflection strategies facilitated learners' visual attention, and controlled the difficulty of processing. Meanwhile, physiological data showed that the learners' reflection was accompanied by stress, and there was no significant difference between the two levels of reflection. Practitioner notes What is already known about this topic Embedding reflections within videos is an effective instructional strategy for online learning which can facilitate students' deep learning. Recent studies have evaluated the effectiveness of reflection mostly through its impact on learning outcomes, yet focusing on the process of reflection is equally valuable. How to choose the level of reflection is critical and challenging. Whether it should combine the processes (including attentional processes and emotional experiences) and outcomes of reflection can be addressed through experimental research. What this paper adds Selecting different levels of reflection (ie, reflection and critical reflection) according to Kember's model and suggesting strategies (ie, retrospective interpretation reports and evaluation reports of problem solving) to guide reflection. The experimental design combined outcomes and processes in order to identify the most appropriate level of reflection in the context of video learning, and both offline and online measurements were taken (including eye tracking and physiological measures). Critical reflection leads to superior learning outcomes and has advantages for attentional processes. Additionally, reflection itself is the main factor influencing participants' stress, and there is no significant difference between the levels of reflection. Implications for practice and/or policy Providing guidance for different levels of reflection (ie, retrospective interpretation reports and evaluation report of problem solving), which helps inform the design of instructional videos and foster learners' reflective awareness. Educators should focus not only on the learning outcomes caused by reflection but also on the learning processes of reflection and the emotional experiences that accompany it, in order to choose an appropriate level of reflection. Whether the teaching goal is knowledge retention or transfer, educators should embed a high level of reflection for learners in instructional videos to promote deep thinking and processing.